Pengaruh Gaya Kepemimpinan, Motivasi Dan Lingkungan Kerja Internal Terhadap Kinerja Karyawan Pada Best Western Mangga Dua Hotel - Ratna Sari; Lisnatiawati Saragih (Universitas Mercu Buana, 2021)
This study aims to analyze the effect of leadership style, motivation and internal work environment on employee performance at Best Western Mangga Dua Hotel. The sample used was 106 respondents. The sampling method uses Saturation Sampling. The method of collecting data uses a survey method, with the research instrument being a questionnaire. Data analysis method uses Partial Least Square. This study proves that leadership style has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Internal Work Environment has a positive and significant effect on employee performance.